Relationship between BMI and Urine pH in Nephrolithiasis Cases in Indonesia - Abdurrahman, Fauzan; Tjahjodjati, Tjahjodjati (Majalah Kedokteran Bandung, 2024)
In nephrolithiasis/urolithiasis, urine pH is thought to modulate kidney stone formation at various stages, including crystallization, growth, aggregation, and retention. Moreover, numerous studies have demonstrated that an increase in Body Mass Index (BMI) correlates with a decrease in urine pH. This study aimed to determine the relationship between BMI and urine pH in cases of nephrolithiasis at Dr. Hasan Sadikin General Hospital Bandung. This was analytical observational study with a cross-sectional design, followed by correlation analysis is carried out. A total of 100 patients from January 2021 to December 2022 have met the inclusion criteria. From the results of the analysis, it was discovered that of the 21 patients with acidic urine pH, 42.11% had normal BMI, 26.32% were grade 1 obese, 15.79% were grade 2 obese, 10.53% were overweight, and 5.26% were underweight. The majority of patients who had normal urine pH also had a normal BMI (34.18%), followed by 30.38% with grade 1 obesity, 21.52% with grade 1 obesity, and 13.92% with grade 2 obesity. Of the 2 patients with  alkaline urine pH, one person had a normal BMI and another had an overweight BMI. The results of the chi-square test presented a p value of >0.05, thus no significant relationship is observed between urine pH and BMI in nephrolithiasis patients.